Diagnostic test study of the skyline view for dorsal screw protrusion after fixation of distal radius fractures (2016)
Objective: The pronator quadratus (PQ) has important functions such as pronation and robust blood supply of metaphysis. However, PQ repair is difficult when using conventional approach, which is necessary to release PQ for volar plate fixation of distal radius fracture. In addition, anatomical reduction is difficult in patients with distal radius metaphyseal comminution fracture. Therefore, the purpose of this study is to compare the results of volar locking plate fixation using PQ sparing technique and conventional volar approach technique for patients with distal radius metaphyseal comminution fracture.